RELATIONSHIP EDUCATION, INCOME, KNOWLEDGE AND PUBLIC ATTITUDES WITH UTILIZATION OF COMMUNAL MCK - Purnama Wirawan; Abdul Razak; Indang Dewata (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2017)
Environment sanitation, public and private communal latrines have been built in densely populated coastal areas with the aim to collect a means of bathing, washing, and toilet. The purpose of this research to determine the relationship of knowledge and attitudes about the use of communal latrines in fishermen settlement Kelurahan Teluk Kabung Selatan of Bungus Teluk Kabung District. Methods research is analytic with cross sectional design and the sample was of 150 people is the head of the family. The Korelasi statistical test indicated was known to have a significant correlation between knowledge society with the use of communal latrines and there is no correlation between people's education, revenue, and attitudes, to the use of Communal toilets. It is necessary to raise awareness to make the most of available Communal Communal MCK by way of extension about its importance to utilize Communal MCK for self health and environmental health.Keywords : Knowledge, Attitude, Utilization, Comunal MCK.